The Mediastinopleurostomy in the diagnosis of thoracic diseases - Bertullo, Hugo; Brandolino, Mario; Carriquiry, Guillermo; Etchandy, Hugo; Sanjinés, Aníbal (Cirugía del Uruguay, 1983)
The authors analyze their experience in 41 mediastinopleurostomies. The diagnostic value of the procedure in mediastinal processes located before lhl• aerial tree is pointed out. No mortality is found in this s(•ri(•.